Allocation of more reproductive resource to egg size rather than clutch size of gregarious desert locust (Schistocerca gregaria) through increasing oogenesis period and oosorption rate. (January 2022) - Maeno, Koutaro Ould; Piou, Cyril; Ghaout, Saïd
Graphical abstract: Highlights: Crowded desert locusts produce fewer but larger eggs than isolated ones. Oocyte and ovarian growth rates were almost similar between isolated and crowded conditions. Crowded females prolonged the oogenesis period and produced larger eggs than isolated females. Crowded females showed increased oosorption rates and reduced clutch sizes. Abstract: The desert locust, Schistocerca gregaria, shows a density-dependent reproductive trade-off by laying fewer but larger eggs in crowded conditions (gregarious phase) than in isolated conditions (solitarious phase). However, the physiological mechanisms controlling reproductive resource allocation remain unclear. We examined how egg production processes, including ovulation timing (i.e., oogenesis period), oocyte and ovarian growth rates, and oosorption rate (resorbing developing terminal oocytes), regulate reproductive outputs (egg biomass per clutch, egg size, and clutch size) during a reproductive cycle in S. gregaria by rearing them either under isolated or crowded conditions. We observed a common density-dependent negative correlation between egg size and clutch size, with no significant difference in egg biomass between the two rearing conditions. Dissection of female locusts after different days of oviposition revealed that the daily oocyte growth rate was almost similar between the two rearing conditions, but crowd-reared females ovulated later than isolated-reared ones, resulting in further oocyte growth in the former. Terminal oocytes were renewed by previous penultimate oocytes at the onset of a new reproductive cycle, and oosorption mainly occurred at an early stage in both rearing conditions; however, crowd-reared locusts displayed higher levels of oosorption compared to their isolated-reared counterparts. Crowding induced a high oosorption rate, resulting in a reduced clutch size and a prolonged oogenesis period, which in turn allowed oocytes to intake more yolk, which was probably recycled via oosorption. These results suggest that the length of the oogenesis period and oosorption rate are manipulated by maternal density, and these physiological modifications interactively regulate reproductive trade-off in S. gregaria .